Prospects for fertility preservation: the ovarian organ function reconstruction techniques for oogenesis, growth and maturation in vitro - Hu, Bai; Wang, Renjie; Wu, Di; Long, Rui; Ruan, Jinghan; Jin, Lei; Ma, Ding; Sun, Chaoyang; Liao, Shujie (Frontiers in Physiology, 2023)
Today, fertility preservation is receiving more attention than ever. Cryopreservation, which preserves ovarian tissue to preserve fertility in young women and reduce the risk of infertility, is currently the most widely practiced. Transplantation, however, is less feasible for women with blood-borne leukemia or cancers with a high risk of ovarian metastasis because of the risk of cancer recurrence. In addition to cryopreservation and re-implantation of embryos, in vitro ovarian organ reconstruction techniques have been considered as an alternative strategy for fertility preservation. In vitro culture of oocytes in vitro Culture, female germ cells induction from pluripotent stem cells (PSC) in vitro, artificial ovary construction, and ovaria-related organoids construction have provided new solutions for fertility preservation, which will therefore maximize the potential for all patients undergoing fertility preservation. In this review, we discussed and thought about the latest ovarian organ function reconstruction techniques in vitro to provide new ideas for future ovarian disease research and fertility preservation of patients with cancer and premature ovarian failure.